2018
DOI: 10.3389/fpsyt.2018.00244
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Convergent Validity and Time Invariance of Default Mode Network Deviations in Early Adult Major Depressive Disorder

Abstract: There is substantial variability across studies of default mode network (DMN) connectivity in major depressive disorder, and reliability and time-invariance are not reported. This study evaluates whether DMN dysconnectivity in remitted depression (rMDD) is reliable over time and symptom-independent, and explores convergent relationships with cognitive features of depression. A longitudinal study was conducted with 82 young adults free of psychotropic medications (47 rMDD, 35 healthy controls) who completed cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 60 publications
2
33
0
Order By: Relevance
“…Subsets of these samples have been reported in prior work, including from MH091811 awarded to Langenecker (Bessette et al, 2018;Bhaumik et al, 2017;DelDonno et al, 2017;Jacobs et al, 2014Jacobs et al, , 2016Jenkins et al, 2017;Rao et al, 2016;Stange et al, 2017), MH086517 awarded to Monk and Phan (Hamm et al, 2014;Wu et al, 2016), UIC CCTS UL1TR000050, Mind and Life Foundation, and Klingenstein Third Generation Foundation Fellowship awarded to Jacobs Peters et al, 2016). Data is also present from MH101487 (awarded to Langenecker).…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsets of these samples have been reported in prior work, including from MH091811 awarded to Langenecker (Bessette et al, 2018;Bhaumik et al, 2017;DelDonno et al, 2017;Jacobs et al, 2014Jacobs et al, , 2016Jenkins et al, 2017;Rao et al, 2016;Stange et al, 2017), MH086517 awarded to Monk and Phan (Hamm et al, 2014;Wu et al, 2016), UIC CCTS UL1TR000050, Mind and Life Foundation, and Klingenstein Third Generation Foundation Fellowship awarded to Jacobs Peters et al, 2016). Data is also present from MH101487 (awarded to Langenecker).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We have previously shown that within the CCN, adolescents (ages 12–17) with a history of depression exhibit increased connectivity (Peters, Burkhouse, Feldhaus, Langenecker, & Jacobs, 2016), whereas the opposite pattern is found among remitted depressed young adults ranging in age from 18 to 23 (Stange et al, 2017). Moreover, when examining cross-network connectivity patterns, remitted depressed adolescents exhibited increased connectivity between the SEN and DMN (Peters et al, 2016), while young adults in remission from MDD exhibited stable and reliable hyperconnectivities of the DMN and SEN with the CCN (Bessette et al, 2018; Jacobs et al, 2014). Thus, taken together, these previous studies suggest that developmental stage may impact the pattern of network connectivity among individuals with a history of depressive and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal scan time depends on multiple factors, including the metrics of RSFC, the scope of the connectivity (ranging from voxel-wise to whole-brain connectivity), the tradeoff between the quantity of data and participant-related factors such as fatigue, motion, and sleepiness (Tomasi, Shokri-Kojori, & Volkow, 2017). Studies have recommended a single scan session between 7 (Tomasi et al, 2017) to 13 min (Bessette et al, 2018;Birn et al, 2013) for obtaining reliable resting-state data.…”
Section: Discussionmentioning
confidence: 99%
“…First, PCC connectivity was somewhat attenuated to the CCN and enhanced to the SN, compared to other seeds, particularly the antHPF. Perhaps this pattern reflects that cortisol is differentially relevant to ventral and dorsal sub-components of the DMN (Bessette et al, 2018;Buckner et al, 2008). The antHPF seeds may more closely mirror results from the amygdala and sgACC because of density in MR and GR receptors, which are more sparsely distributed in the PCC (Sapolsky, 2000;Tsigos and Chrousos, 2002).…”
Section: Discussionmentioning
confidence: 99%